Significance of Project Identification and Formulation to Sustainable Capacity Development Interventions - Boelen, Martijn G.J. (My University, 2011)
Capacity Development interventions can lack effectiveness if the intervention is not aligned with the abilities of the receiving organisation. Triggered by the personal experiences of the researcher, this research paper explores which issues must be dealt with in the identification and formulation phase of a Capacity Development project. The purpose of this study is to come up with an overview of these issues to assist all practitioners in this field to formulate potentially effective and sustainable project plans. From the literature review it was concluded that the issues can be grouped in three categories: the vision of the receiving organisation and issues internal and external to this organisation. It appeared that particularly the learning culture and the abilities of management to change the organisation and lead the staff are very important issues that must be properly sorted out before the project can start. From the field research it appeared that weaknesses in the receiving organisation with regards to the issues that came out of the literature review had indeed a negative effect on the results of the researched project. One of the most important conclusions of the research is that the identification and formulation phase should not be underestimated and that the success of the project depends largely on a proper and thorough approach in this stage. The most attention must be paid to all circumstances surrounding the actual technical capacity that will be developed. Main recommendation for the target group of this research is therefore to take enough time to gather information in this phase and adapt the project to the abilities of the receiving organisation which should become clear as a result of this information. It might even be necessary to have a project to strengthen these abilities preceding the actual Capacity Development intervention
MM thesis - P&DM
Keywords: Capacity development; Project management